2000
DOI: 10.1590/s0100-879x2000000700012
|View full text |Cite
|
Sign up to set email alerts
|

The hemolytic component of cancer anemia: effects of osmotic and metabolic stress on the erythrocytes of rats bearing multifocal inoculations of the Walker 256 tumor

Abstract: Cancer anemia is classified as an anemia of chronic diseases, although it is sometimes the first symptom of cancer. Cancer anemia includes a hemolytic component, important in the terminal stage when even transfused cells are rapidly destroyed. The presence of a chronic component and the terminal complications of the illness limit studies of the hemolytic component. A multifocal model of tumor growth was used here to simulate the terminal metastatic dissemination stage (several simultaneous inoculations of Walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
7
0
8
Order By: Relevance
“…Desde então ele vem sendo mantido em diversos laboratórios no mundo inteiro como um recurso valioso no auxílio à pesquisa básica em oncologia. São numerosos os trabalhos sobre o tumor de Walker, seu comportamento biológico, suas alterações bioquímicas e efeitos metabólicos 2,3 , e sua utilização em modelos experimentais no pulmão 4 , estômago 5 , rim 6 , cavidade oral 7 e fígado 8 . Nosso objetivo é o estudo de um modelo experimental para Walker em bexiga.…”
Section: Introductionunclassified
“…Desde então ele vem sendo mantido em diversos laboratórios no mundo inteiro como um recurso valioso no auxílio à pesquisa básica em oncologia. São numerosos os trabalhos sobre o tumor de Walker, seu comportamento biológico, suas alterações bioquímicas e efeitos metabólicos 2,3 , e sua utilização em modelos experimentais no pulmão 4 , estômago 5 , rim 6 , cavidade oral 7 e fígado 8 . Nosso objetivo é o estudo de um modelo experimental para Walker em bexiga.…”
Section: Introductionunclassified
“…We had previously reported that in intact rats bearing the progressive A variant of the W256 cancer the rapid terminal destruction of RBC was associated with a decrease or no change in RBC osmotic fragility (8). In contrast, rats inoculated with the AR tumor variant systematically developed a temporary anemia associated with a marked increase in RBC osmotic fragility at the beginning of tumor regression.…”
Section: Discussion Cancer Anemiamentioning
confidence: 98%
“…Macro-and/or microscopic alterations of bone marrow have long been ruled out as factors involved in cancer anemia in humans (23) and rats (4). In the terminal stage of cancer, RBC are rapidly destroyed, even transfused ones, at a rate of up to five times the physiological rate, without an increase in RBC osmotic fragility (8). This terminal anemia is not temporary but continues to increase with a very high correlation (r 2 = 0.86) with the other severe systemic effects involved in terminal general failure (8).…”
Section: Discussion Cancer Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Two variants of this tumor have been previously reported as W256 A and B (Guaitani et al, 1982), which are currently known by their growth capacity and lethality after subcutaneous (sc) injection in Wistar rats. This lethality is associated to the severe homeostatic disturbances induced by the W256 tumor, which includes anorexia (Rettori et al, 1995;Guaitani et al, 1982), anemia (Zucker et al, 1977;Vido et al, 2000), thymus atrophy (Rettori et al, 1995) and hydro electrolyte disturbances with glomerular filtration and tubular function alterations (Toal et al, 1960;Morrison, 1971;Rettori et al, 1995;Guimarães et al, 1999;Rettori et al, 2000). Nevertheless, spontaneous W256 tumor regression can occur.…”
Section: Introductionmentioning
confidence: 99%